2020
DOI: 10.7759/cureus.8740
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorder Increases Risk of Traumatic Brain Injury-Related Hospitalization: Insights From 3.8 Million Children and Adolescent Inpatients

Abstract: We conducted a cross-sectional study to identify the demographic predictors of traumatic brain injury (TBI), and the risk of association of psychiatric comorbidities including alcohol use disorder (AUD) and TBI-related hospitalizations in the children and adolescent population. Methods We included 3,825,523 children and adolescent inpatients (age 8-18 years) using the nationwide inpatient sample (NIS) database (2010-2014), and 61,948 inpatients had a primary diagnosis of TBI. These inpatients were grouped by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…(13), it is also related to traffic accidents (14). Study has shown that the rate of traumatic brain injury leading to hospitalization is 50% more in child and adolescents who are current drinker compared to non-drinker (15). In this case, our results of rising trend in the rate of current drinker and binge drinker in the adolescents should be given serious attention.…”
Section: Discussionmentioning
confidence: 81%
“…(13), it is also related to traffic accidents (14). Study has shown that the rate of traumatic brain injury leading to hospitalization is 50% more in child and adolescents who are current drinker compared to non-drinker (15). In this case, our results of rising trend in the rate of current drinker and binge drinker in the adolescents should be given serious attention.…”
Section: Discussionmentioning
confidence: 81%
“…In the general population, the neural changes and resulting cognitive and psychological impairments occurring after TBI are strong predictors of substance use, misuse, and development of SUD (Graham and Cardon, 2008;Weil et al, 2016;Beaulieu-Bonneau et al, 2018;Olsen and Corrigan, 2021), and contribute to poorer treatment outcomes (Corrigan and Deutschle, 2008;Graham and Cardon, 2008). However, the cause-and-effect relationship between TBI and substance use is complex and hard to parse as substance use is both a risk factor for, and sequelae of, TBI (Nikoo et al, 2017;Eskander et al, 2020). Nonetheless, there is evidence that brain injury often remains undiagnosed among IPV-EW, as substance misuse and mental health issues mask brain injury symptoms, thereby precluding effective assessment and treatment for brain injury (Banks, 2007;Haag et al, 2022).…”
Section: Brain Injury and Substance Usementioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) and numerous research groups have identified populations at higher risk of sustaining severe brain injury in the United States, including racial and ethnic minorities, 9 10 those with psychiatric disorders, 11 12 13 substance use disorders, 14 15 16 military service members and veterans, 17 18 19 20 21 people who are undomiciled, 22 23 24 living in correctional or detention facilities, 25 26 27 refugees, 26 28 and victims of domestic violence. 29 30 31 32 As we will later explore, people who live in rural areas or who are underinsured are less likely to receive appropriate or timely services following brain injury.…”
Section: Preinjury Phasementioning
confidence: 99%